2019
DOI: 10.3389/fnins.2019.00264
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Exercise Ameliorates Depression-Like Behavior in the Rats With Prenatal Dexamethasone Exposure: The Role of Hippocampal Mitochondria

Abstract: Prenatal exposure to synthetic glucocorticoids (sGCs) can increase the risk of affective disorders, such as depression, in adulthood. Given that exercise training can ameliorate depression and improve mitochondrial function, we sought to investigate whether exercise can ameliorate depression-like behavior induced by prenatal sGC exposure and mitochondria function contributes to that behavior. At first, we confirmed that prenatal dexamethasone (Dex) administration in late pregnancy resulted in depression-like b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Swimming can alleviate the depression-like behavior of rat offspring, which is associated with mitochondrial movement related to O-GlcNAc transferase (OGT), which includes the PINK1/Parkin and AKT/GSK3 signaling pathways. Another study (103) has also shown that this effect was related to the improvement of mitochondrial morphology and function, which illustrated that hippocampal ATP production and mitochondrial membrane potential of rats in the exercise group increased significantly, while the production of mitochondrial superoxide decreased significantly; also, the high HPA activity in rats with depression was reversed. Endurance exercise has also been shown to stimulate mitochondrial biogenesis in a wide range of tissues (74).…”
Section: Other Physiological Factorsmentioning
confidence: 90%
“…Swimming can alleviate the depression-like behavior of rat offspring, which is associated with mitochondrial movement related to O-GlcNAc transferase (OGT), which includes the PINK1/Parkin and AKT/GSK3 signaling pathways. Another study (103) has also shown that this effect was related to the improvement of mitochondrial morphology and function, which illustrated that hippocampal ATP production and mitochondrial membrane potential of rats in the exercise group increased significantly, while the production of mitochondrial superoxide decreased significantly; also, the high HPA activity in rats with depression was reversed. Endurance exercise has also been shown to stimulate mitochondrial biogenesis in a wide range of tissues (74).…”
Section: Other Physiological Factorsmentioning
confidence: 90%
“…MitoTEMPO is a novel cell-penetrating antioxidant targeting mitochondria, containing a hydrophobic tetramethylpiperidine (TEMPO) group and a lipophilic triphenylphosphine cation (TPP+). It can penetrate mitochondria and remove ROS produced by mitochondria [40][41][42][43]. Therefore, we selected MitoTEMPO as a targeted scavenger of mitochondrial ROS and C57BL/6J mice who had long-term exercise and MitoTEMPO were selected as the research objects to explore the effects of skeletal muscle mitochondrial health in mice to investigate the relationship between mitochondrial health and UPRmt and mitochondrial ROS in long-term regular exercise of skeletal muscle MitoTEMPO.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Kim and Hwang discussed that a short-term (3 weeks) treadmill training was able to improve oxidative parameters in rats with cardiomyopathy [ 90 ], while the work of Cechetti et al demonstrated that a moderate-intensity treadmill training mitigated oxidative damage in the rat hippocampus, therefore contributing to cognitive improvements [ 91 ]. According to the results of Wu et al, 9 weeks of treadmill exercise has beneficial effects against depression-like behavior in rats [ 92 ]. In addition, 3 weeks of forced running has also been shown to be beneficial in doxorubicin-induced liver disease through the normalization of oxidative stress markers [ 93 ].…”
Section: Aerobic Exercise Modelsmentioning
confidence: 99%